Analisis Keberlakuan Peraturan Pemerintah Turunan Undang-Undang Cipta Kerja Pasca Putusan Inkonstitusional Bersyarat - Rozaq, Moh. Fatkhur; Mediawati, Noor Fatimah (Web of Scientist International Scientific Research Journal, 2024)
It should be noted that the Job Creation Law No.11/2020 has caused many contradictions and differences of opinion. This is because at the time of drafting the law, it was considered too hasty to implement the omnibus law in Indonesia and very close to stakeholders, which shows that there is no openness of information and discussion space with the wider community. Anwar Usman, chairman of the legal panel emphasized that the Job Creation Law is formally flawed and therefore declared unconstitutional with conditions. Then some time ago it was passed by the DPR into Law No.6/2023 concerning the Stipulation of Government Regulation in Lieu of Law No.2/2022 concerning Job Creation. The amendment of Perpu on Job Creation No. 2/2022 in the labor cluster does not fully provide protection for workers, instead what happens is a reduction in normative rights as workers/laborers. As the theory of the rule of law, legal protection, human rights, labor law and political formation should be able to create protection for workers, which we know so far the rights of workers have always been weaker than employers.